Evaluasi Teknis Pembangunan Ruang Kelas Dua Lantai pada Sekolah Dasar Berlahan Terbatas: Perspektif Perencana - Hendro Damanra; Bambang Istijono (Fakultas Teknik Universitas Cenderawasih, 2026)
Limited land availability is a major constraint in developing school infrastructure in active urban educational facilities. This study evaluates the classroom development plan at SDN 39 Lubuklinggau from the perspective of a planner, focusing on land limitation, functional needs, safety, constructability, and long-term building performance. A descriptive-evaluative approach was applied through technical observation, document review, alternative assessment, weighted scoring, and risk analysis. The results indicate that horizontal expansion is constrained by limited open space and may reduce internal circulation, student activity areas, and emergency space. Three alternatives were compared: horizontal expansion, building rearrangement, and a two-storey classroom scheme. The two-storey alternative obtained the highest score of 84, compared with 61 for rearrangement and 56 for horizontal expansion. However, its feasibility depends on further soil investigation, structural design, staircase and evacuation safety, utility coordination, construction phasing, and strict site safety control. The study recommends that the planner prioritize detailed site measurement, geotechnical investigation, detailed engineering design, construction safety planning, and post-construction functional evaluation. A vertical classroom strategy can be considered a rational solution for land-constrained schools when supported by accountable technical planning and integrated project control.